2004
DOI: 10.3346/jkms.2004.19.1.155
|View full text |Cite
|
Sign up to set email alerts
|

Glial Choristoma in the Middle Ear and Mastoid Bone: A Case Report

Abstract: Heterotopic brain tissue usually involves extracranial midline structures of the head and neck such as nose, nasopharynx, and oral cavity. Its occurrence in the non-midline structures, including middle ear, is rare. We described a 50-yr-old-man with heterotopic glial tissue in the middle ear and mastoid bone. The patient presented with progressive hearing loss for 8 yr. There was no history of congenital anomalies, trauma, or ear surgery. Computed tomography revealed a mass-like lesion with soft tissue density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 13 publications
0
14
0
4
Order By: Relevance
“…1 Unrecognized remote trauma can also be considered. 9 In this case, although there was a bony defect at the tegmen tympani, the dura was intact and a connection with the central nervous system was not established. Histologically, these lesions are composed of neurons and glial tissue, with some associated chronic inflammation and gliosis.…”
Section: Discussionmentioning
confidence: 92%
“…1 Unrecognized remote trauma can also be considered. 9 In this case, although there was a bony defect at the tegmen tympani, the dura was intact and a connection with the central nervous system was not established. Histologically, these lesions are composed of neurons and glial tissue, with some associated chronic inflammation and gliosis.…”
Section: Discussionmentioning
confidence: 92%
“…The diagnosis of heterotopia versus encephalocele needs the knowledge of radiologic and operative findings of the patients [13]. CT scan and conventional radiographic studies have limitations in detecting small bony defects or narrow stalk like connections across the skull base.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by several predisposing factors likely to cause defects in the tegmen tympani, including a previous trauma or surgery or concomitant infection. However, our literature review revealed that defects in the tegmen based on pre-operative CT or intraoperative findings were reported in only 8/32 cases [567891011]. Direct evidence of a connection with the brain parenchyma, such as an intraoperative CSF leak, was confirmed in only 2/32 cases [7].…”
Section: Discussionmentioning
confidence: 99%